1970
DOI: 10.1084/jem.131.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Immune Response to a Characterized Antigenic Determinant of the Tobacco Mosaic Virus Protein

Abstract: The following peptides have previously been shown to bind specifically with antibodies to TMVP: (a) An eicosapeptide representing residues 93–112 of TMVP and having the sequence Ileu-Ileu-Glu-Val-Glu-AspNH2-GluNH2-Ala-AspNH2-Pro-Thr-Thr-Ala-Glu-Thr-Leu-Asp-Ala-Thr-Arg. (b) Its C-terminal decapeptide. (c) Its C-terminal pentapeptide. (d) N-octanoyl-C-terminal-tripeptide. (e) (Lys)4-C-terminal-pentapeptide. (f) (Lys)7 C-terminal-pentapeptide. The present communication deals with the investigation of several para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

1971
1971
1975
1975

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…Several investigators have demonstrated a correlation between delayed cutaneous hypersensitivity and inhibition of migration of cells from capillary tubes (15,(21)(22)(23). The findings with glucagon peptides are consistent with those of others inasmuch as each peptide which elicited a skin reaction also inhibited cell migration, and their effectiveness in the two assays showed a roughly quantitative correlation (Table II).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Several investigators have demonstrated a correlation between delayed cutaneous hypersensitivity and inhibition of migration of cells from capillary tubes (15,(21)(22)(23). The findings with glucagon peptides are consistent with those of others inasmuch as each peptide which elicited a skin reaction also inhibited cell migration, and their effectiveness in the two assays showed a roughly quantitative correlation (Table II).…”
Section: Discussionsupporting
confidence: 78%
“…However, we failed to find a correlation between skin reactivity or inhibitory capacity on the one hand, and the ability to transform cells in vitro on the other, since the NM peptide was decidedly active in the two former assays but exerted no palpable effect on DNA synthesis (Table III). This contrasts with several reports (21,24), but is in agreement with others which demonstrated a dissociation between these activities (23,25). It is unclear whether the activities represent different expressions by the same cells or expressions by different populations of cells.…”
Section: Discussioncontrasting
confidence: 56%
“…Both delayed skin reactions and lymphocyte transformation are reflections of cellular immunity which is known to be more exacting in its recognition of the immunizing antigen than is binding by humoral antibody (12,13). Since autologous or homologous IgG in either the aggregate-free or aggregated state caused no in vitro stimulation of lymphocytes from rheumatoid patients, rheumatoid factor may be induced by a different but structurally similar antigen or IgG in a form not exactly duplicated by heat aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showing a dissociation between antigen-induced mediator production in one cell population and proliferation in another population deserve further exploration with a common cell population (22,23).…”
Section: Discussionmentioning
confidence: 99%